SENS-IS, a 3D reconstituted epidermis based model for quantifying chemical sensitization potency: Reproducibility and predictivity results from an inter-laboratory study. (April 2016) - Cottrez, Françoise; Boitel, Elodie; Ourlin, Jean-Claude; Peiffer, Jean-Luc; Fabre, Isabelle; Henaoui, Imène-Sarah; Mari, Bernard; Vallauri, Ambre; Paquet, Agnes; Barbry, Pascal; Auriault, Claude; Aeby, Pierre; et al.
Abstract: The SENS-IS test protocol for the in vitro detection of sensitizers is based on a reconstructed human skin model (Episkin) as the test system and on the analysis of the expression of a large panel of genes. Its excellent performance was initially demonstrated with a limited set of test chemicals. Further studies (described here) were organized to confirm these preliminary results and to obtain a detailed statistical analysis of the predictive capacity of the assay. A ring-study was thus organized and performed within three laboratories, using a test set of 19 blind coded chemicals. Data analysis indicated that the assay is robust, easily transferable and offers high predictivity and excellent within- and between-laboratories reproducibility. To further evaluate the predictivity of the test protocol according to Cooper statistics a comprehensive test set of 150 chemicals was then analyzed. Again, data analysis confirmed the excellent capacity of the SENS-IS assay for predicting both hazard and potency characteristics, confirming that this assay should be considered as a serious alternative to the available in vivo sensitization tests. Highlights: The SENS-IS assay quantifies skin sensitization potency. The SENS-IS assay is easily transferable. The ring study shows excellent reproducibility over 90%. Specificity, sensitivity and accuracy, analyzed on 150 chemicals, were above 90%.